2005
DOI: 10.1148/rg.255055001
|View full text |Cite
|
Sign up to set email alerts
|

Median Arcuate Ligament Syndrome: Evaluation with CT Angiography

Abstract: The median arcuate ligament is a fibrous arch that unites the diaphragmatic crura on either side of the aortic hiatus. The ligament usually passes superior to the origin of the celiac axis. However, in some people, the ligament inserts low and thus crosses the proximal portion of the celiac axis, causing compression and sometimes resulting in abdominal pain. The diagnosis of clinically significant celiac axis compression, referred to as median arcuate ligament syndrome, is traditionally made with conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
267
0
22

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(292 citation statements)
references
References 10 publications
3
267
0
22
Order By: Relevance
“…However, recent implementation of MDCT has enabled the production of fast, thin-slice, multiplanar, reformatted and 3D angiographic images. Also, high-resolution images can be obtained for the aorta and its branches and also for the mesenteric vascular structures [6]. In our study with 64-slice CT, the multiplanar reformatted 3D angiographic images perfectly demonstrated the vascular anatomy and compression without any need for conventional angiography, which is a more invasive technique.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…However, recent implementation of MDCT has enabled the production of fast, thin-slice, multiplanar, reformatted and 3D angiographic images. Also, high-resolution images can be obtained for the aorta and its branches and also for the mesenteric vascular structures [6]. In our study with 64-slice CT, the multiplanar reformatted 3D angiographic images perfectly demonstrated the vascular anatomy and compression without any need for conventional angiography, which is a more invasive technique.…”
Section: Discussionsupporting
confidence: 52%
“…This ligament may cause a compression and abdominal pain while passing anterior to the proximal part of the celiac truncus [6]. The MALS was initially described by Harjola, in 1963 [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, they described a classical triad of chronic postprandial abdominal pain, epigastric bruit, and weight loss. 3,4 Extrinsic compression of the celiac trunk by the MAL occurs in 10% to 24% of patients. 1 Usually, patients are asymptomatic and the classical triad is not always present, presumably due to collateral supply from the superior mesenteric circulation.…”
Section: Discussionmentioning
confidence: 99%